The Impact of Energy-Intensive Industries on the Carbon Emissions : A Review (Comprehensive Journal of Science, 2025)
Industrial de-carbonization is becoming a crucial part of climate mitigation initiatives due to the global shift to a low-carbon economy. Global warming is largely caused by greenhouse gas (GHG) emissions, primarily carbon dioxide (CO₂), which are produced by industrial sectors such as steel, cement, and petrochemicals. The emission profiles and decarburization paths of major industrial sectors are reviewed in this study, which also evaluates present effects and potential mitigation techniques. Although clinker manufacturing and combustion processes pose a problem to the cement industry, which accounts for around 8% of worldwide CO₂ emissions, the sector is working to reduce emissions through the use of carbon capture technology, energy efficiency, and supplemental cementitious materials (SCMs). In addition, the steel sector, which contributes between 7 and 9% of the world's CO2 emissions, is investigating switching from conventional blast furnaces to renewable energy-powered electric arc furnaces (EAFs), although obstacles like infrastructure and technical scalability still exist. Furthermore, despite technical breakthroughs, emissions from the petrochemical sector—particularly from plastics and fertilizers continue to rise. Promising emission reductions are provided by circular economy activities, such as chemical and mechanical recycling, as well as bio-based feedstocks. The article assesses the significance of key technologies, including electrification, energy efficiency enhancements, integration of renewable energy, carbon capture, use, and storage (CCUS), and material substitution through circular economy practices, in accelerating industrial de-carbonization. Despite the great promise of these breakthroughs, high capital costs, unclear policies, inadequate infrastructure, and inconsistent technological maturity prevent their widespread adoption. In order to encourage low carbon transitions, policy and regulatory frameworks such as international climate agreements, government subsidies, and emissions pricing are crucial. Finally, achieving net-zero emissions and meeting climate objectives by the middle of the century will require a multifaceted strategy that incorporates technical innovation, regulatory assistance, and systemic industry reform.
Keywords: Carbon, industry, decarburization, greenhouse gas.